Application of imidazolium-based ionic liquid as bulk liquid membrane in phenol removal / Ng Yee Sern - Ng, Yee Sern (2011)

(untitled)
Performance of imidazolium-based ionic liquid membranes [Bmim][PF6], [Bmim][NTf2] and [Bmim][FAP] on phenol removal was evaluated under room temperature by using batch bulk liquid membrane system. The results showed that all ionic liquids tested formed stable membranes and exhibited better solvent recoveries in comparison to organic membrane solvent, dichloromethane with [Bmim][NTf2] showing the highest extraction and stripping efficiencies of 94.18% and 73.39%, respectively after 300 min experiment due to its relatively higher hydrogen bond basicity strength and adequate hydrophobicity. Following the finding, [Bmim][NTf2] was further analyzed to determine the effect of the feed phase pH, feed concentration, NaOH concentration and stirring speeds on liquid membrane behavior and performance. Based on the experimental results, a phenol transport mechanism which is similar to that of organic liquid membranes was proposed for [Bmim][NTf2] based liquid membrane. [Bmim][NTf2] possessed similar behavior as organic membrane solvent whereby it favoured molecular phenol extraction to phenolate anion. Besides, high phenol dissolution capacity of this ionic liquid also prevented membrane saturation even in high phenol concentration solution treatment. An optimization study on the significant parameters using Central Composite Design showed that maximum extraction and stripping efficiencies of 96.21% and 98.10% were achieved under the conditions of feed phase pH ≈6.5, 300ppm phenol concentration, 0.5M NaOH concentration, 135rpm membrane stirring speed and 255rpm aqueous stirring speed. This study has proven that [Bmim][NTf2] is a better choice than kerosene and dichloromethane.